Oral Health in Low-Income Older Adults in Korea. Issue 2 (2nd April 2016) - Lee, Young-Shin; Kim, Hee-Gerl; Hur, Jung-Yi; Yang, Kyeongra
ABSTRACT: Oral diseases among older adults are prevalent and a major public health problem, but public attention regarding this matter is quite limited. Many older adults experience limited access to oral care services. The study aimed to describe characteristics of oral health conditions, perceived oral health status, and oral health practices and to examine factors related to living status and accessibility to dental health care among 9, 660 low-income older adults living in a suburban city in Korea. Approximately 42% of low-income older adults lived alone; 68% perceived their oral health as either excellent or good; and 31% reported difficulty accessing dental services. Lack of accessibility to oral care services was significantly more common in older adults with low incomes, living alone, having poor oral conditions, poor self-perceived oral health, and poor tooth-brushing behavior. Strategies to promote access to dental care services for underserved older adults should be developed to prevent further oral problems and their impact on overall health conditions.